2012
DOI: 10.1128/jcm.00532-12
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Foreign Body in the Urinary Bladder Mimicking a Parasitic Worm

Abstract: We report an unusual case of a foreign body removed from the urinary bladder of a 63-year-old male which mimicked a parasitic worm. The foreign body was identified as an artificial fishing worm by morphological comparison to a similar commercially produced product and by infrared spectrum analysis. CASE REPORTA 63-year-old male presented to his urologist with complaints of sudden-onset urinary urgency, pelvic pain, and dysuria with decreased force of his urinary stream. He had had four suspected urinary tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Structure greatly resemble the morphology of the larvae of Dioctophyma renale had been reported in the renal pelvis of two mice, in the third one, cross section of the parasitic larvae were reported to be encysted in the renal fat close from the renal pelvis. Analysis of all available literature revealed that parasite was always accidentally diagnosed as the case in our report (Schmitt et al, 2012;Katafigiotis et al, 2013). According to many animal/ human cases, the infection can be explained by indiscriminate eating habits of these animals (Kommers et al, 1999) that occurred by eating infected worms or paratenic hosts as fish, crayfish or frogs in which the larvae become encapsulated in the tissue.…”
Section: Discussionmentioning
confidence: 62%
“…Structure greatly resemble the morphology of the larvae of Dioctophyma renale had been reported in the renal pelvis of two mice, in the third one, cross section of the parasitic larvae were reported to be encysted in the renal fat close from the renal pelvis. Analysis of all available literature revealed that parasite was always accidentally diagnosed as the case in our report (Schmitt et al, 2012;Katafigiotis et al, 2013). According to many animal/ human cases, the infection can be explained by indiscriminate eating habits of these animals (Kommers et al, 1999) that occurred by eating infected worms or paratenic hosts as fish, crayfish or frogs in which the larvae become encapsulated in the tissue.…”
Section: Discussionmentioning
confidence: 62%
“…After the primary and secondary screenings were conducted as shown in Fig. 5 , we obtained a total of 17 relevant case reports reporting self-insertion of foreign bodies into the urethra and bladder [3 , 4 , 6 , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . The details and characteristics of each report are shown in Table 1 .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The objects reported varied from inorganic to organic objects. Two of the most interesting objects reported consist of 4 kidney beans and an object resembling a worm with an encrustation [6 , 12] . Most reports consist of tubular objects, including cables similar to the earphone wire in this case report.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations